2016
DOI: 10.1097/dcc.0000000000000187
|View full text |Cite
|
Sign up to set email alerts
|

Women’s Sexual Issues After Myocardial Infarction

Abstract: The results of this review demonstrate that women's post-MI sexual activity is affected by many concerns. The concerns may be a knowledge deficit related to not receiving necessary consultation on this topic. Nurses, as first-line care givers, can provide appropriate consultation and education for patients post-MI. As a result, breaking taboo imposed by cultural barriers, personal assumptions, or lack of confidence on giving sexual consultation may ultimately help patients to improve their quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…The effect of infertility on the mental health of women can lead to high rates of depression, anxiety, and disappointment with life. Depression and other psychological problems in infertile women are barriers to seeking medical counselling, while disappointment with life can lead to reduced screening behaviours [24], [25].…”
Section: Discussionmentioning
confidence: 99%
“…The effect of infertility on the mental health of women can lead to high rates of depression, anxiety, and disappointment with life. Depression and other psychological problems in infertile women are barriers to seeking medical counselling, while disappointment with life can lead to reduced screening behaviours [24], [25].…”
Section: Discussionmentioning
confidence: 99%
“…• Sexual concerns are prevalent after myocardial infarction, and women are inclined to conceal them because of cultural barriers. 22 • Ability to climb 2 flights of stairs is generally considered adequate fitness for sexual activity. 23 Heart failure…”
Section: Myocardial Infarctionmentioning
confidence: 99%
“…The results of studies have shown that changes in symptoms of depression are concomitantly associated with sexual function fluctuations on a daily basis [23]. In addition, sexual dysfunction is more reported in depressed women [33]. In general, women living in rural areas experience more distress or turmoil, compared to women inhabiting urban areas, and cultural issues in villages limit the acceptance of mental health services in these regions [34].…”
Section: Introductionmentioning
confidence: 99%